Penerapan Modul Pengendali Sistem Robotik Berbasis STEM di Sekolah Menengah Kejuruan - Rio Bina Guna; Risfendra Risfendra (Jurnal Pendidikan Teknik Elektro, 2022)
This research is motivated by the lack of learning resources for Robotic System Control subjects and the learning model used is still teacher-centered. This Robotic System Control subject is still a new subject in the 2013 curriculum, so teachers only use learning modules that already exist on the internet without using learning models. Besides, students do not have additional learning resources other than the modules that have been given by the teacher. This study aims to develop a Robotic System Control module using a valid, practical and effective STEM Learning Model. This type of research is the research and development method. The method used is a 4-D model consisting of the stages of definition (Define), design (Design), development (Development) and deployment (Dessiminate). The research subjects were students of class XI TEI SMKN 1 West Sumatra. The data collection technique used an evaluation sheet in the form of a questionnaire for validity and practicality data. while objective tests were used for effectiveness data. The results showed that (1) the validity test of the Robotic System Controller module using the STEM learning model had been tested and declared valid. (2) the practicality test of the Robotic System Controller module using the STEM learning model has been tested and declared practical. (3) testing the effectiveness of the Robotic System Control module using the STEM learning model has been tested and declared effective. Based on the results of the study, it can be concluded that the development of the Robotic System Control module using the STEM learning model is valid, practical, and effective so that it is feasible to use.